2008
DOI: 10.1063/1.2955786
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic diffusion of point defects in metals under a biaxial stress field simulation and theory

Abstract: We study the diffusion anisotropy (DA) of point defects in fcc and bcc metals in the presence of an applied biaxial stress. The DA depends sensitively on both the crystalline structure and the crystallographic direction in which the stress is applied. For example, interstitials in fcc metals diffuse faster in the plane of the compressive stress than normal to it when the stress is applied to the (001) plane, but they diffuse slower in-plane than out-of-plane when the stress is applied in the (111) plane. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Defects such as dislocations or interfaces act as sinks for point defects but also generate a strain field, which alters diffusion properties [10][11][12][13] . By breaking the symmetry of the crystal structure, the strain field induces anisotropy of the diffusion properties 10,11,13 The Onsager matrix-which relates chemical potential gradients to atomic fluxes-is then a second-rank tensor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Defects such as dislocations or interfaces act as sinks for point defects but also generate a strain field, which alters diffusion properties [10][11][12][13] . By breaking the symmetry of the crystal structure, the strain field induces anisotropy of the diffusion properties 10,11,13 The Onsager matrix-which relates chemical potential gradients to atomic fluxes-is then a second-rank tensor.…”
mentioning
confidence: 99%
“…By breaking the symmetry of the crystal structure, the strain field induces anisotropy of the diffusion properties 10,11,13 The Onsager matrix-which relates chemical potential gradients to atomic fluxes-is then a second-rank tensor. The Onsager matrix of diverse cubic structures has been computed [14][15][16][17][18][19][20][21][22] .…”
mentioning
confidence: 99%
“…KineCluE allows for an essentially seamless application of the SCMF cluster-expansion method to strained systems, thus widely improving the state-ofthe-art models for computing fully strain-dependent transport matrices. Strain-dependent diffusion coefficients have been measured by molecular dynamics [88] and by Monte Carlo simulations [89], but it has been shown that measuring the elasto-diffusion tensor with the latter method is tricky [90]. Previous analytical models allowing for such kind of calculations were based on:…”
Section: Transport Coefficients In Strained Systemsmentioning
confidence: 99%
“…Garnier et al [20] found that the strain field near an edge dislocation in Ni causes complex flow patterns for Si solutes and vacancies. Chan et al [21] performed atomic simulations in face-centered cubic (FCC) Pt and Cu to show that the anisotropic diffusion of vacancies and self-interstitials under strain strongly depends on the crystal structure and the crystallographic directions in which the strain is applied.…”
Section: Introductionmentioning
confidence: 99%